Lithological controls of the Mg isotope composition of the Lena River across seasons and its impact on the annual isotope flux to the Arctic Ocean - Mavromatis, V; Porcelli, D; Andersson, PS; Korets, MA; Pokrovsky, OS (Elsevier, 2024)
Given the importance of permafrost regions in providing the major elements to the Arctic Ocean, and the vulnerability of these regions to ongoing climate change due to permafrost thaw and landscape modifications, assessing the magnitude and characterizing the factors governing isotope compositions in river waters across seasons and space is of high priority. Towards identifying possible environmental controlling factors (climate, vegetation, rock lithology) and quantifying annual fluxes of dissolved Mg isotopic signatures in large Arctic rivers located in the continuous permafrost zone, here we measured hydrochemical and Mg isotope compositions of the Lena River main channel and its various tributaries over different seasons of the year. In general, we did not find evidence of any statistically significant (p < 0.05) correlation between δ26Mg and main physico-geographical parameters of the river watersheds (temperature, permafrost, type of vegetation). The exception is the decrease in riverine δ26Mg values that was accompanied by an increase in the carbonate rock proportion in the watershed, whereas an opposite trend was observed for the abundance of terrigenous and silicate rocks. An incontestable control of dolomite rocks on Mg isotope signature in the Lena River was also supported by decreasing δ26Mg values with increasing Dissolved Inorganic Carbon (DIC) concentration, as also observed for other Artic River basins. This relationship was mostly pronounced during the high-flow period, when secondary Mg silicate formation in soils and underground waters and so the terrestrial uptake of Mg were the lowest. In the Lena River main channel, the lowest δ26Mg values (−1.5 ± 0.05 ‰) were observed during autumn-winter (September to March), probably reflecting a dominant role of underground reservoirs and subsurface soil weathering of isotopically light Precambrian dolomites. The mean δ26Mg values of the Lena River during two months of spring (−1.02 to −1.28 ‰), 4 months of summer baseflow (−1.30 ‰) and 6 months of winter yields a mean discharge-weighted annual value of −1.26 ± 0.05 ‰. This number coincides with the value of summer baseflow reported in earlier works. Therefore, like in the recently studied Yenisey River basin, the Mg isotope signature of the Lena River water likely stems from a mixture of carbonate (−2.0 ≥ δ26Mg ≥ −2.5 ‰) and silicate (0 ≥ δ26Mg ≥ −0.2 ‰) rocks in its watershed. We also argue that the discharge-weighted mean annual isotopic signature of an element in the Artic rivers can be reasonably approximated by a single sampling campaign during summer baseflow. This allows cost-effective assessment of mean riverine isotopic signatures of other elements in both small and large rivers to the Arctic Ocean.